Prospective Gain or Actual Cost? Arab Civilian and Military Captives in the Light of Byzantine Narrative Sources and Military Manuals from the 10th Century - Wierzbiński, Szymon (Studia Ceranea, 2018)
For the Byzantine emperors of the 10th century, the eastern front was the crucial one, due to the constant struggle with the Abbasid Caliphate. In the course of this conflict – from which Byzantium emerged victorious – the capturing and enslaving of soldiers and civilians alike was an everyday reality. The main objective of this paper is to define the role of prisoners of war in the strategy and tactics of Byzantine generals. First, I will attempt to determine whether the latter treated the captives as a potential gain under various aspects (i.e. financial, prestige-related, or diplomatic). Next, I will focus on those situations in which prisoners were nothing more than a burden. With the help of narrative sources and military manuals, I will try to clarify why both sides occasionally decided to execute their captives in certain episodes of the 10th century Arab-Byzantine conflict. Finally, I will specify how Byzantine generals made use of prisoners in order to get the upper hand over their Arab rivals.